Atlas : geography, architecture and change in an interdependent world - Butcher, Melissa (London. : Black Dog Architecture, 2012)
Atlas: Geography, Architecture and Change in an Interdependent World helps readers find their way through the practical and ethical challenges presented by globalisation and global environmental change. Atlas: Geography, Architecture and Change in an Interdependent World combines recent thinking on human geography and architecture on global environmental change issues, setting out to develop a reinterpretation of cartography and a reframing of sustainability. The aim is to find a "re-drawing of the earth" and the "making of new maps". With a focus on the growth and remaking of cities it offers an innovative mix of essays and shorter texts, original artworks and distinctive re-mappings. The Atlas arises out of a unique collaboration between scholars and practitioners from architecture and human geography. The project is in collaboration with the Open Space Research Centre at The Open University and is a collaboration between academics from the Geography discipline OU, the School of Architecture, University of Sheffield and researchers at the New Economics Foundation.
Keywords: Architecture; Globalization; Human geography; Sustainable development